DISINFORMATION, POLARISATION AND DIGITAL CAMPAIGNS: A COMPARATIVE STUDY OF POLITICAL COMMUNICATION IN THE ONLINE SPHERE - Sugiharto, Agus; Wijayanto, Wijayanto; Kushandajani, Kushandajani; Hasfi, Nurul (JWP (Jurnal Wacana Politik), 2026)
Digital political campaigns have become a key phenomenon in contemporary politics. They significantly transform the patterns of communication between political parties, candidates, and voters. This study aims to analyze the development, dynamics, and implications of digital political campaigns on voter behavior as well as political communication strategies in the era of information technology. Using a qualitative approach through literature review of scholarly articles, the results show that digital political campaigns offer high efficiency in reaching a broad audience and enable the personalization of messages based on big data and predictive analytics. However, this practice also brings new challenges, such as the spread of disinformation, political polarization, and manipulation of public opinion. This method employs a qualitative literature review of peer-reviewed studies (2020–2025) and, where relevant, clarifies the analytical lens used, such as thematic or categorical analysis. This approach enhances methodological transparency without adding excessive length. These findings affirm that digital transformation in political campaigns is not merely a change in medium, but also a paradigm shift in political communication. Therefore, transparent digital governance, adaptive regulation, and political digital literacy for society are essential to ensure that digital political campaigns are conducted ethically and strengthen democratic values.